La Simulación de costos ambientales como prevención en la empresa sostenible (2020)
The article summarizes research work “simulated environmental costs, as a tool for the prevention and assurance of sustainable enterprise”. In fact, accounting has been reaffirming its importance not only in the economic, but social and environmental development of the company and the state, going from being considered as a data management technique, to being decisive in the orientation of any type of organization. The topic of Environmental Accounting (CA) arises in the need to have a tool to demonstrate environmental sustainability and social responsibility; but despite its importance, environmental policy does not have appropriate environmental accounting information systems and standards. A timely exploration of the environmental impact and the cost that can be generated in business activity with the appropriation of the policies established by the Ministry of Environment and Sustainable Development contributes towards the positioning of the company as sustainable and socially responsible organization.